Analisis Dampak Nilai Tukar dan Penanaman Modal Asing terhadap Nilai Ekspor Indonesia Periode 1990-2018 - Siska Aryanto; Syaparuddin Syaparuddin; Siti Aminah (Jurnal Ekonomi Aktual, 2021)
This study aims to analyze the impact of the exchange rate and foreign investment on Indonesian exports from 1990-2018. The data used is secondary data sourced from the Central Statistics Agency Indonesia, Bank Indonesia, and the Investment Coordinating Board. Data were analyzed using multiple linear regression models. The results showed that the development of the exchange rate, foreign investment, and exports tend to fluctuate. The exchange rate and foreign investment simultaneously have a significant impact on Indonesia's exports. In addition, the exchange rate and foreign direct investment partially have a significant impact on Indonesia's exports.